Upaya pencegahan resiko disfungsi keluarga melalui permainan kotak edukasi berbasis Talking Pen - Niki Moktika Dwi Megawati; Reynanda Putra Pratama; Nisriani Uswatunnisa; Putri Wandana; Ahmad Dzaky Zain; Adi Irawan Setiyanto (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2020)
One aspect of outcome in national expansion is the development of a prosperous family (UU No. 52 year 2009). Each parent is obliged to care, educate, guide the lives of children to adulthood. Therefore, in the PP No. 21 year 1994 family function includes functions of religion, social and cultural, affection, protection, socialization and education, economic and environmental development. The purpose of carrying out this program, specifically: 1) Provides additional knowledge about the function and role of family through educational games "GANSIA" that can be played by all family members, 2) Creation of communities that are able to accomplish the function of family optimally. The objective of this program established in RW 06 Kecamatan Sagulung where there are 1,061 inhabitants. The majority of residents work for industrial workers, shipyards, teachers and merchants. The implementation method of this program will be made by pretest and post test method. The potential results of this program are: 1) Establishment of community "Rumah Permata", moreover as a counseling amenity, mentoring family welfare education, and the establishment of productive household enhancement, 2) Potential for obtaining Intellectual Property Rights is a patent for the invention of an educational box game accompanied by Talking Pen accordingly themed with the local sagacity of Kota Batam. Keywords: Disfungstion, Education games, Prosperous